Prevalence of stunting and associated factors among public primary school pupils of Bahir Dar city, Ethiopia: School-based cross-sectional study. - Getasew Mulat Bantie; Amare Alamirew Aynie; Kidist Hailu Akenew; Mahlet Tilahun Belete; Eyerusalem Teshome Tena; Genet Gebreselasie Gebretsadik; Aynalem Nebebe Tsegaw; Tigist Birru Woldemariam; Ashenafi Abate Woya; Amare Alemu Melese; Agumas Fentahun Ayalew; Getenet Dessie (PLoS ONE)
Background Stunting is a well-established child-health indicator of chronic malnutrition, which reliably gives a picture of the past nutritional history and the prevailing environmental and socioeconomic circumstances. Objective To investigate the prevalence of stunting and associated factors among public primary school children of the Bahir Dar city. Method A cross-sectional study was carried out from March to June 2019. Data were coded and entered into the Epi-Data and exported to SPSS version 23 software. The pupil was stunted if the height- for-age was ≤ -2 SDs from the median growth standards according to the WHO. A descriptive summary was computed using frequency, percent, mean, median and standard deviation. A simple logistic regression model was fitted to identify associated factors between the independent variables and the dependent variable at a 95% confidence interval (CI) and p-value <0.05. Results 370 primary school pupils were included in the study with the mean age of 10.15 (± 2.23 SD) years. 51.6% of the pupils were females. The total prevalence of stunting was 15.13% (95%CI; 11%, 19%). The burden of stunting was higher in the age group of 11 years and older. Pupil's age older than 11 years (AOR = 15. 6; 95%CI; 3.31, 73.45; p-value < 0. 001) and male sex (AOR = 7. 07; 95%CI: 2.51, 19.89; p-value < 0. 0002) were significantly associated with stunting. Conclusion The prevalence of stunting was relatively lower than the regional estimated stunting level. Older age and male sex were significantly associated with stunting.